2013
DOI: 10.3329/kyamcj.v1i1.13300
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Tuberculosis

Abstract: DOI: http://dx.doi.org/10.3329/kyamcj.v1i1.13300KYAMC Journal Vol.1(1) July 2010, 16-20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…These results are consistent with the findings of Darbari A et al 2 (58%), Krishnanand et al 9 (54.8%), Tripathi PB et al 10 (55.4%), Zea MI et al 11 (64%), Saaiq M et al 12 (61.37%), Shimy GG et al 13 (45.56%), Islam MB et al 14 (75%) and Rabbi ANMA et al 15 (54.54%).…”
Section: Age-wise Distribution Of Gitb Casessupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with the findings of Darbari A et al 2 (58%), Krishnanand et al 9 (54.8%), Tripathi PB et al 10 (55.4%), Zea MI et al 11 (64%), Saaiq M et al 12 (61.37%), Shimy GG et al 13 (45.56%), Islam MB et al 14 (75%) and Rabbi ANMA et al 15 (54.54%).…”
Section: Age-wise Distribution Of Gitb Casessupporting
confidence: 82%
“…Ileocaecal junction was the most common site involved in GITB cases in the present study, which is in concordant with the studies done by Sharma YR et al 16 (28%), Islam MB et al 14 (51.6%), Ibrahim M et al 22 (38.46%), Tripathi PB et al 10 (50.9%), Rabbi ANMA et al 15 (56.52%) and Zea MI et al 11 (72.22%). The exact explanation for more frequent involvement of the ileocaecal region is unknown, but it may be due to a variety of factors such as increased rate of fluid/electrolyte absorption, abundance of lymphoid tissue in the form of Peyer's patches, physiological stasis and minimal digestive activity at the ileocaecal region.…”
Section: Anatomic Sites Involved In Gitbsupporting
confidence: 82%
“…Kamal et al 5 reported 22% EPTB patient among 514 study patient whereas 46.9% EPTB patients were female and lymph node tuberculosis was most prevalent in their study. Rabbi et al 20 reported 33 case of abdominal tuberculosis in Bangladesh with 54.54% female patient. Sultana et al 21 reported 60 cases of cutaneous tuberculosis where 38.3% was skin tuberculosis.…”
Section: Discussionmentioning
confidence: 99%